SOBRE UNA ASOCIACION DE DINOSAURIOS Y OTRAS EVIDENCIAS DE VERTEBRADOS DEL CRETACICO SUPERIOR DE LA REGION DE LA CANDELARIA, PROV. DE SALTA, ARGENTINA (Ameghiniana, 2013)
The remains of fossil vertebrates found in the Southern end ofLa Candelaria Hills, Province of Salta, are described and discussed. The presence of three associated dinosaurs is determined in Arroyo Morterito (Los Blanquitos Formation): Laplatasaurus sp., a Sauropoda indet. and a new theropod, Unquillosaurus ceibalii. Pucapristis branisi (Batoidea, Pristidae) and a Carnosauria indet. come from Aguas Calientes (Yacoraite Formation), both of which are represented only by a tooth each, The Upper Cretaceous age of Los Blanquitos and Yacoraite Formations is reaffirmed.